2015
DOI: 10.1371/journal.pone.0122314
|View full text |Cite
|
Sign up to set email alerts
|

Association of Household and Community Socioeconomic Position and Urbanicity with Underweight and Overweight among Women in Pakistan

Abstract: BackgroundSimilar to other developing countries, Pakistan is going through a rapid nutrition transition where shift from underweight to overweight and obesity is occurring. In this paper, we report on the relationship of household socioeconomic position (SEP), community SEP and urbanicity with under- and over-weight categories of BMI among Pakistani women.MethodsWe analyzed data on 4,767 women ages 15-49 years enrolled in a nationally representative Pakistan Demographic Health Survey (PDHS) conducted in 2012-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 43 publications
10
20
0
Order By: Relevance
“…The results demonstrate the co-existence of dual burden of underweight and overweight in both males and females. These findings are consistent with data from South Asian neighboring countries [ 27 29 ]. For example, a Bangladeshi study reported that 36% of adult women and 29.1% men where underweight and 24.4% of women and 20.5% of men were overweight or obese [ 27 ].…”
Section: Discussionsupporting
confidence: 92%
“…The results demonstrate the co-existence of dual burden of underweight and overweight in both males and females. These findings are consistent with data from South Asian neighboring countries [ 27 29 ]. For example, a Bangladeshi study reported that 36% of adult women and 29.1% men where underweight and 24.4% of women and 20.5% of men were overweight or obese [ 27 ].…”
Section: Discussionsupporting
confidence: 92%
“…The study found that roughly one in three women (35%) of reproductive age in Nepal were either overweight or obese. This is almost similar to the prevalence of overweight and obesity (measured using the Asia-specific cutoff and a nationally representative sample) among women of reproductive age in neighboring South Asian countries, including Bangladesh (36%), Pakistan (39%), and Myanmar (38.7%) [16,36,37]. The prevalence of overweight and obesity was higher among women who were older, residing in Province No.…”
Section: Discussionsupporting
confidence: 69%
“…On the other hand, a tendency of being underweight was low in younger age-group. Although studies from Ethiopia [44], Pakistan [29] and Bangladesh [22] showed a similar observation, our study purports unbiased estimation showing more likelihood of being overweight and obesity in older women. Younger age-group women reported having low BMI in developing countries than compared to the developed countries.…”
Section: Discussionsupporting
confidence: 59%
“…We included women as our study population, keeping in mind that women in the LMICs are at higher risk of undernutrition. Studies from Nepal [27], and from other south Asian countries, including Bangladesh [22], and Pakistan [29] corroborated a high prevalence of poor nutritional status among women than compared to males. Despite concerted programmatic interventions aiming at improving the nutritional status of women, this has always been a challenge in Nepal.…”
Section: Discussionmentioning
confidence: 91%